Nature preschools and forest kindergartens : the handbook for outdoor learning - Sobel, David, 1949-; Bailie, Patti; Finch, Ken; Kenny, Erin (Redleaf Press, 2016)
"Nature Preschools and Forest Kindergartens walks you through the European roots of the concept to the recent resurgence of these kinds of programs in North America. These experts provide the framework to understand the concepts and build a learning community that stimulates curiosity and inquisitiveness in a natural environment. This helpful guide provides the curriculum ideas and guidance needed to foster special gifts in children, and gives you the nuts and bolts of running a successful nature preschool business"--